Entrepreneurship and Innovation Toolkit - Swanson, Lee; Open Textbook Library (Open Textbook Library, 2017)
This book is designed for upper year undergraduate students and graduate students studying fundamental entrepreneurship concepts.
Entrepreneurship and Innovation ToolkitAcknowledgementsIntroduction -- Chapter 1 - Introduction to Entrepreneurship -- Chapter 2 - Opportunity Recognition and Design Thinking -- Chapter 3 - Evaluating Entrepreneurial Opportunities -- Chapter 4 - Business Models -- Chapter 5 - Business Planning -- Chapter 6 - Financing Entrepreneurship -- Chapter 7 - Business Set-Up, Start-Up, and Growth -- Chapter 8 - Strategic Entrepreneurship -- Chapter 9 - Innovation and Entrepreneurship -- Chapter 10 - The Entrepreneurial Environment -- ReferencesThe Language of Entrepreneurship
In English.
Description based on print resource
Keywords: Business -- Textbooks; Management -- Textbooks